PENGARUH PENGGUNAAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR IPS -EKONOMI PADA SISWA KELAS X SMK GLOBAL NUSANTARA HAL-SEL. - Narilah A Tuara (Program Studi Pendidikan Ekonomi STKIP Kie Raha Ternate, 2021)
ABSTRACT This study aims to determine the effect of the use of the Role Playing Method on the learning outcomes of students in class X SMK Global Nusantar Hal-Sel. The research method used is Quasi Experimental Design and nonequivalent control group design research design. The population is 60 people, consisting of class XA 30 students and class XB 30 students. Based on the post-test data analysis using the t test, it was obtatined that t count was 2.0723> t tabel 2.0453. the shows that there is an influence of the role playing method on the social studies learing outcomes of students. The magnitude of the influence is calculated using the formula for the effect size of 041 with the medium category. So it can be concluded thet the role playing method has a moderate effect on the socional studies learning outcome of class X SMK Global Nusantara Halmahera Selatan students